SPATIAL VARIABILITY OF HEAVY SAND MINERALS IN AL-KARMA REGION, AL-ANBAR GOVERNORATE, IRAQ - Alkhalil, Shireen Mudhafar Ali; Almashhadani, Bilal Majeed Kareem; Hamad, Abdulghafour Ibrahim; Mohammed, Sawsan Ahmed (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
This study aims to analyze the mineral composition in the AL-Karmah area in the Anbar Governorate in western Iraq, within the flood plain of the Euphrates River, bounded between 33°23'00" and 33°25'00" north, and 43°53'00" and 43°56'00" East, with an area of 54451.14 hectares. 25 surface samples with a depth of 0-30 cm were collected. Bromoform  was used to separate heavy minerals  from light minerals. The mineral composition  was using diagnosis polarized microscope. The ArcMap GIS software analyzed the spatial distribution and produced maps using IDW method. The results of the geographical analysis of the distribution of heavy minerals  in the soils of the Karma area showed the dominance of specific ratios of several minerals. Iron oxides (45.76–48.17%) covered the largest area, amounting to 59.04%. While chlorite percentage was (7-10%) in 87.72% of the whole area. Garnet  (5-8%) dominated 86.91%, and zircon (3-6%) dominated 96.34%. Pyroxene (5-8%) covered 63.08%, and amphibole (3-5%) scored 93.08%. As for the epidote (4-6%), it amounted to 97.64%. Muscovite (3-6%) was found in 92.39%, while biotite (4-6%) dominated 96.82% of the area.